2008
DOI: 10.1038/hdy.2008.76
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of phenotypic plasticity: QTL analysis in barley, Hordeum vulgare

Abstract: Phenotypic plasticity is the variation in phenotypic traits produced by a genotype in different environments. In contrast, environmental canalization is defined as the insensitivity of a genotype's phenotype to variation in environments. Despite the extensive literature on the evolutionary significance and potential genetic mechanisms driving plasticity and canalization, few studies tried to unravel the genetic basis of this phenomenon. Using both simulations and real data from barley (Hordeum vulgare), we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 66 publications
10
92
0
Order By: Relevance
“…Similar results were obtained in drought and nutrient stress experiments, in which phenotypic plasticity was much higher in epiRILs than in the Col-0 wild type and highly heritable (Zhang et al, 2013). However, PP is also observed in conventional RIL populations (Lacaze et al, 2009;Tétard-Jones et al, 2011;ElSoda et al, 2014). It is difficult to compare the epigenetic with the genetic contribution to phenotypic plasticity, as epigenetic variation might contribute to phenotypic variation in conventional RIL populations when the epigenetic variation associates with the genetic markers (Schmitz et al, 2013a).…”
Section: Dna Hypomethylation Amplifies Phenotypic Plasticitysupporting
confidence: 76%
See 2 more Smart Citations
“…Similar results were obtained in drought and nutrient stress experiments, in which phenotypic plasticity was much higher in epiRILs than in the Col-0 wild type and highly heritable (Zhang et al, 2013). However, PP is also observed in conventional RIL populations (Lacaze et al, 2009;Tétard-Jones et al, 2011;ElSoda et al, 2014). It is difficult to compare the epigenetic with the genetic contribution to phenotypic plasticity, as epigenetic variation might contribute to phenotypic variation in conventional RIL populations when the epigenetic variation associates with the genetic markers (Schmitz et al, 2013a).…”
Section: Dna Hypomethylation Amplifies Phenotypic Plasticitysupporting
confidence: 76%
“…All PP QTLs coincided with QTLs explaining variation in the same morphological traits under control conditions. This indicates that the regulatory gene(s) underlying the QTLs are sensitive to variation in the environment and that modification of methylation profiles determines to some extent plasticity (Lacaze et al, 2009). In rice (Oryza sativa), a mutation in a gene leading to increased DNA methylation on repetitive sequences and decreased histone acetylation resulted in high expression variation in different environments, illustrating the regulation of PP through epigenetic processes .…”
Section: Dna Hypomethylation Amplifies Phenotypic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing Nipponbare with CSSLs, we confirmed that root plasticity was affected by the intensities of drought stress and also affected by the genotypes indicating that such plastic root response is genetically controlled (Niones et al 2015). By using these tools, the genetic control of phenotypic plasticity has been clarified through the precise quantitative evaluation and measurement of root plasticity with minimal ef f ects of genetic confounding (Lacaze et al 2009, Sandhu et al 2016.…”
Section: Discussionmentioning
confidence: 69%
“…some genes are expressed only under some circumstances, or some gene function is only relevant under some environments) (Gardner & Latta, 2006;Lacaze et al, 2008). Alternatively, it may be due to the existence of a 'plasticity gene' that affects the magnitude of the plastic response independent of the QTL that affect variation in trait value (Schlichting & Pigliucci, 1993).…”
Section: Discussionmentioning
confidence: 99%